Public service motivation research: lessons for practice - Christensen, Robert K.; Perry, James L.; Paarlberg, Laurie (2017)
Public service motivation research has proliferated in parallel with concerns about how to improve the performance of public service personnel. However, scholarship does not always inform management and leadership. This article purposefully reviews public service motivation research since 2008 to determine the extent to which researchers have identified lessons for practice. The results of the investigation support several lessons-among them using public service motivation as a selection tool, facilitating public service motivation through cooperation in the workplace, conveying the significance of the job, and building leadership based on public service values. These results are important because they offer evidence that the field is coalescing around tactics that managers and leaders can use to address enduring concerns about employee motivation in the public sector. They also prompt us to articulate ideas that can guide a tighter integration of research and practice moving forward. - Reproduced.
Keywords: Research; Public services; Motivation